2008
DOI: 10.1097/rlu.0b013e31818866bf
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Somatostatin Receptor Scintigraphy in the Management of Tumor-induced Osteomalacia

Abstract: We highlight the impact of somatostatin receptor evaluation in the management of TIO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 24 publications
4
43
0
Order By: Relevance
“…As a result of the presence of somatostatin receptors on these tumors, it has been suggested that octreotide, a synthetic somatostatin analogue, would be useful in decreasing FGF-23 secretion [20]. Although there is one case report regarding use of octreotide as mitigating therapy before definitive treatment [20], few clinicians have been successful in repeating the initial success with this technique [3,4,13,16]. One of our patients underwent a trial of octreotide chemotherapy, but this was unsuccessful.…”
Section: Discussionmentioning
confidence: 97%
“…As a result of the presence of somatostatin receptors on these tumors, it has been suggested that octreotide, a synthetic somatostatin analogue, would be useful in decreasing FGF-23 secretion [20]. Although there is one case report regarding use of octreotide as mitigating therapy before definitive treatment [20], few clinicians have been successful in repeating the initial success with this technique [3,4,13,16]. One of our patients underwent a trial of octreotide chemotherapy, but this was unsuccessful.…”
Section: Discussionmentioning
confidence: 97%
“…Somatostatin receptors have been found to be present in many TIO lesions, and 111-indium octreotide has a high affinity for the somatostatin receptor, especially subtype 2 and to a lesser extent subtype 5 [13,15]. As with FDG PET/CT, emphasis should be placed on making sure these imaging tests cover the entire body from head to toe, including the hands and feet.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that there are 'blind' spots in this functional imaging modality, for example, the brain uptake of FDG-PET tracer may obscure intracranial tumors, and uptake of octreotide in the liver and spleen may obscure potential lesions within these organs [3,4,13,15].…”
Section: Discussionmentioning
confidence: 99%
“…Since many tumors causing osteomalacia are small and difficult to locate, radiologic methods are often employed to localize the tumors. Several different methods have been used including magnetic resonance imaging (48-50), technetium 99m sestamibi scintigraphy (51-55), radiolabeled octreotide scanning (8,(56)(57)(58)(59)(60)(61), and F-18 fluorodeoxyglucose positron emission tomography with computed tomography (8,(62)(63)(64)(65)(66)(67). In some small series, authors have claimed sensitivities of 60-80% with radiolabeled octreotide scanning and PET/CT scanning.…”
Section: Radiological Investigationsmentioning
confidence: 99%